2008
DOI: 10.1039/b809949a
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polymers for controlled release of cisplatin

Abstract: Hyperbranched polymers based on a polyether and polyester have been modified and used as macromolecular ligands for the anticancer drug cisplatin, giving controlled release of the drug over 7 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 14 publications
1
52
0
Order By: Relevance
“…The spectra also exhibited two pronounced peaks at 3292 and 1385 cm -1 , revealing the absorptions of N-H stretching from cisplatin ligands (Pt-NH 2 ), and the chelation of the COO-Pt stretch, respectively [47,48]. In addition, a reduction in absorbance of the carbonyl (C=O) stretch of COOH at 1704 cm -1 relative to the amide C=O band at 1633 cm -1 (the difference between relative intensity in (a) and (b) in Figure 11) is consistent with the prediction that some of the -COOH groups would react with the Pt atoms in a ligand exchange reaction [49]. Dynamic light scattering was also employed to confirm size changes in the polymer induced by the conjugation (Figure 12).…”
Section: Preparation Of the Cisplatin-loadedsupporting
confidence: 72%
“…The spectra also exhibited two pronounced peaks at 3292 and 1385 cm -1 , revealing the absorptions of N-H stretching from cisplatin ligands (Pt-NH 2 ), and the chelation of the COO-Pt stretch, respectively [47,48]. In addition, a reduction in absorbance of the carbonyl (C=O) stretch of COOH at 1704 cm -1 relative to the amide C=O band at 1633 cm -1 (the difference between relative intensity in (a) and (b) in Figure 11) is consistent with the prediction that some of the -COOH groups would react with the Pt atoms in a ligand exchange reaction [49]. Dynamic light scattering was also employed to confirm size changes in the polymer induced by the conjugation (Figure 12).…”
Section: Preparation Of the Cisplatin-loadedsupporting
confidence: 72%
“…Moreover, such system can deliver simultaneously two or more drugs for the combination therapy [16,17]. It was reported that linear water-soluble polymers, block copolymers able to form micelles [13][14][15][16][17], and branched polymers have been studied as nanocarriers for chemotherapeutic agents [18]. Such nanosystems containing cis-Pt can be efficiently accumulated in the tumors, thereby enhancing the antitumor action.…”
Section: Introductionmentioning
confidence: 99%
“…These dendrimers have included PAMAM, polyglycerol [22], poly(propyleneimine) [23], and thiol-yne derived [21] dendrimers with the active components of both cisplatin [17] and oxaliplatin [16] and a novel DNA intercalating platinum complex [15]. In some cases the platinum drugs are attached non-reversibly to the dendrimer through coordination to the amine groups, but in most cases the drugs were attached either by electrostatic attraction [15], or through reversible but direct coordination of the platinum atom to the terminal carboxylate groups [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Previously dendrimers have been examined sporadically as delivery vehicles for several different types of platinum drugs and complexes [15][16][17][18][19][20][21][22]. These dendrimers have included PAMAM, polyglycerol [22], poly(propyleneimine) [23], and thiol-yne derived [21] dendrimers with the active components of both cisplatin [17] and oxaliplatin [16] and a novel DNA intercalating platinum complex [15].…”
Section: Introductionmentioning
confidence: 99%